Studi Etnobotani Tumbuhan Berkhasiat Obat Di Desa Trimodadi, Lampung Utara - Arinanda, Tesya Atika; Kurniawan, Ardyan Pramudya (Universitas Medan Area, 2023)
Ethnobotany is a science that studies the relationship between humans and plants. Treatment using medicinal plants is still widely used by the community in Trimodadi Village. This study aims to determine the types of plants used, plant organs used, plant processing processes, how to use plants, the origin of public knowledge and calculate the use value and important value of medicinal plants. This study used the Snowball Sampling method with in-depth interview techniques. The results of the study found 58 species from 30 families of medicinal plants. The families Zingiberaceae and Poaceae have the largest number of species. The most widely used habitus is Herba. Plant parts used are leaves, rhizomes, stems, fruits, flowers, bulbs, roots, stalks, sap, shoots, and seeds. The processing method is boiled, brewed, ground, without processing, grated, kneaded, baked, vegetable, and burned. How to use is drunk, smeared, eaten, rubbed, pasted, soaked, dripped, washed and evaporated. The highest UVs are Sambiroto (Andrographis paniculata Burm. F.) 0.6 UVs and the highest INP value is Ginger (Zingiber officinale Roscoe.) 90% INP.